2020
DOI: 10.6018/sportk.412431
|View full text |Cite
|
Sign up to set email alerts
|

Time and reglamentary analysis during high level wheelchair basketball competition: training conclusions

Abstract: Uno de los aspectos fundamentales para determinar la exigencia física en un deporte colectivo es el análisis de la duración de las acciones de juego, las pausas reglamentarias y su origen. Por ello, el objetivo del presente estudio fue analizar la incidencia de las fases de juego y de pausa en el baloncesto en silla de ruedas, así como la duración y frecuencia de los eventos que generan dichas pausas. Se realizó una observación sistemática con un instrumento de registro desarrollado ad hoc sobre un total de 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
2
3
0
2
Order By: Relevance
“…In contrast to this reduced presence in ambulant basketball, in our study an important presence of the intermediate zone is observed aligns with the results of Vanlandewijck et al (2004). Again, with the proxemical analysis of the defensive field, but in this case linked to the zone dimension, the relevance in wheelchair basketball of short duration sequences and counterattack is evident (Pérez-Tejero et al, 2020). Specifically, it has been detected that the presence of the defensive outside favours effective counterattack situations, like what happens in ambulant basketball (Ortega & Gómez, 2009); whereas the defensive intermediate zone presents effective and ineffective situations; and defensive paint is revealed as an ineffective zone for initiating a counterattack coinciding with the results of Refoyo and colleagues (2009) in ambulant basketball.…”
Section: Retrospective Lagssupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast to this reduced presence in ambulant basketball, in our study an important presence of the intermediate zone is observed aligns with the results of Vanlandewijck et al (2004). Again, with the proxemical analysis of the defensive field, but in this case linked to the zone dimension, the relevance in wheelchair basketball of short duration sequences and counterattack is evident (Pérez-Tejero et al, 2020). Specifically, it has been detected that the presence of the defensive outside favours effective counterattack situations, like what happens in ambulant basketball (Ortega & Gómez, 2009); whereas the defensive intermediate zone presents effective and ineffective situations; and defensive paint is revealed as an ineffective zone for initiating a counterattack coinciding with the results of Refoyo and colleagues (2009) in ambulant basketball.…”
Section: Retrospective Lagssupporting
confidence: 88%
“…Regarding the retrospective analysis of the dimension Start of the sequence, the results show the relationship of the defensive field with efficacy present in fast and counterattack sequences (Pérez-Tejero et al, 2020). This efficacy is not as clear from the defensive paint.…”
Section: Retrospective Lagsmentioning
confidence: 88%
See 2 more Smart Citations
“…Además, aportan una gran cantidad de información, motivo por el cual han sido analizados en diferentes modalidades deportivas, como el fútbol (Sánchez-Murillo et al, 2021), el tenis (Escudero-Tena et al, 2020), o, el baloncesto convencional (Puente et al, 2015). De la misma manera, en los últimos tiempos, se ha desarrollado el estudio de indicadores de rendimiento en modalidades deportivas para personas con discapacidad, como en Fútbol-7 para personas con parálisis cerebral (Gamonales et al, 2019;Peña-González et al, 2021), Fútbol para personas con ceguera o discapacidad visual (Muñoz-Jiménez et al, 2022), Goalball para personas con ceguera (Muñoz-Jiménez et al, 2021), Rugby en Silla de Ruedas (Gámez-Calvo et al, 2021), o Baloncesto en Silla de Ruedas (en adelante, BSR), para personas con movilidad reducida (Pérez-Tejero & Pinilla-Arbex, 2015).…”
Section: Introductionunclassified